Transcriptional Profile of Mycobacterium tuberculosis in an in vitro Model of Intraocular Tuberculosis - Abhishek, Sudhanshu; Saikia, Uma Nahar; Gupta, Amod; Bansal, Reema; Gupta, Vishali; Singh, Nirbhai; Laal, Suman; Verma, Indu (Frontiers in Cellular and Infection Microbiology, 2018)
Intraocular tuberculosis (IOTB), an extrapulmonary manifestation of tuberculosis of eye has unique and varied clinical presentations with poorly understood pathogenesis. As, it is a significant cause of inflammation and visual morbidity particularly in TB endemic countries, it is essential to study the pathogenesis of IOTB. Clinical and histopathologic evidences studies suggest the presence of Mycobacterium tuberculosis in retinal pigment epithelium (RPE) cells. A human retinal pigment epithelium (ARPE-19) cell line was infected with a virulent strain of M. tuberculosis (H37Rv). Electron microscopy and colony forming units (CFU) assay were performed to monitor the M. tuberculosis adherence, invasion and intracellular replication whereas confocal microscopy was done to study its intracellular fate in RPE cells. To understand the pathogenesis, transcriptional profile of M. tuberculosis in ARPE-19 cells was studied by whole genome microarray. Three upregulated M. tuberculosis transcripts were also examined in human IOTB vitreous samples. Scanning electron micrographs of infected ARPE-19 cells indicated adherence of bacilli which were further observed to be internalized as monitored by transmission electron microscopy. CFU assay showed that 22.7% and 8.4% of the initial inoculum of bacilli adhered and invaded the ARPE-19 cells respectively with an increased fold CFU from 1 dpi (0.84) to 5dpi (6.58). The intracellular bacilli were co-localised with lysosomal- associated membrane protein-1 (LAMP-1) and LAMP-2 in ARPE-19 cells. The transcriptome study of intracellular bacilli showed that most of the upregulated transcripts correspond to genes encoding the proteins involved in processes like adherence (e.g. Rv1759c and Rv1026), invasion (e.g. Rv1971 and Rv0169), virulence (e.g. Rv2844 and Rv0775) and intracellular survival (e.g. Rv1884c and Rv2450c) as well as regulators of various metabolic pathways. Two of the upregulated transcripts (Rv1971, Rv1230c) were also present in the vitreous samples of the IOTB patients. M. tuberculosis is phagocytosed by RPE cells and utilizes these cells for intracellular multiplication with the involvement of late endosomal/lysosomal compartments and alters its transcriptional profile plausibly for its intracellular adaptation and survival. The findings of the present study could be important to understand the molecular pathogenesis of IOTB with a potential role in the development of diagnostics and therapeutics for IOTB.